MicroRNA-150 Suppression of Angiopoetin-2 Generation and Signaling Is Crucial for Resolving Vascular Injury. Issue 2 (February 2016) - Rajput, Charu; Tauseef, Mohammad; Farazuddin, Mohammad; Yazbeck, Pascal; Amin, Md-Ruhul; Avin BR, Vijay; Sharma, Tiffany; Mehta, Dolly
Abstract : Objective—: Increased vascular permeability is a hallmark of sepsis and acute respiratory distress syndrome. Angiopoietin (Ang2) induces vascular leak, and excess Ang2 generation is associated with patient mortality from these diseases. However, mechanisms dampening Ang2 generation during injury remain unclear. Interestingly, microRNA (miR)-150 levels were decreased in septic patients. miR regulate signaling networks by silencing mRNAs containing complementary sequences. Thus, we hypothesized that miR-150 suppresses Ang2 generation and thereby resolves vascular injury. Approach and Results—: Wild-type or miR-150 −/− mice or endothelial cells were exposed to lipopolysaccharide or sepsis, and Ang2 levels, adherens junction reannealing, endothelial barrier function, and mortality were determined. Although Ang2 transiently increased during lipopolysaccharide-induced injury in wild-type endothelial cells and lungs, miR-150 expression was elevated only during recovery from injury. Deletion of miR-150 caused a persistent increase in Ang2 levels and impaired adherens junctions reannealing after injury, resulting thereby in an irreversible increase in vascular permeability. Also, miR-150 −/− mice died rapidly after sepsis. Rescuing miR-150 expression in endothelial cells prevented Ang2 generation, thereby restoring vascular barrier function in miR-150 −/− mice. miR-150 terminated Ang2 generation by targeting the transcription factor, early growth response 2. Thus, early growth response 2 or Ang2 depletion in miR-150 −/− endothelial cells restored junctional reannealing and reinstated barrier function. Importantly, upregulating miR-150 expression by injecting a chemically synthesized miR-150 mimic into wild-type mice vasculature decreased early growth response 2 and Ang2 levels and hence mortality from sepsis. Conclusions—: miR-150 is a novel suppressor of Ang2 generation with a key role in resolving vascular injury and reducing mortality resulting from sepsis. Abstract : Supplemental Digital Content is available in the text.